2011
DOI: 10.1152/japplphysiol.01423.2010
|View full text |Cite
|
Sign up to set email alerts
|

Aging and aerobic fitness affect the contribution of noradrenergic sympathetic nerves to the rapid cutaneous vasodilator response to local heating

Abstract: Sedentary aging results in a diminished rapid cutaneous vasodilator response to local heating. We investigated whether this diminished response was due to altered contributions of noradrenergic sympathetic nerves by assessing 1) the age-related decline and 2) the effect of aerobic fitness. Using laser-Doppler flowmetry, we measured skin blood flow (SkBF) in young (24 ± 1 yr) and older (64 ± 1 yr) endurance-trained and sedentary men (n = 7 per group) at baseline and during 35 min of local skin heating to 42°C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 41 publications
(62 reference statements)
3
46
1
Order By: Relevance
“…Black et al [92] used L-NAME (an NO synthase inhibitor) during acetylcholine infusions to block NO production and demonstrated that, in initially sedentary elderly individuals, increase in vascular responsiveness following 12 and 24 weeks of aerobic training was induced by the increase in action of NO in the skin. There are similar results in a longitudinal study [93] although a cross-sectional study reported no effects [94].…”
Section: Diabetes and Its Complicationssupporting
confidence: 62%
“…Black et al [92] used L-NAME (an NO synthase inhibitor) during acetylcholine infusions to block NO production and demonstrated that, in initially sedentary elderly individuals, increase in vascular responsiveness following 12 and 24 weeks of aerobic training was induced by the increase in action of NO in the skin. There are similar results in a longitudinal study [93] although a cross-sectional study reported no effects [94].…”
Section: Diabetes and Its Complicationssupporting
confidence: 62%
“…The BT was administered via microdialysis at a concentration of 10 mM for 60 min at a rate of 4 μl min −1 (Hodges et al 2009b;Tew et al 2011b). The adequacy of the BT blockade was tested at the end of the experiment by 3 min of whole-body cooling, reducing T sk from 34 to 31…”
Section: Drugsmentioning
confidence: 99%
“…While it may seem counter-intuitive to assign a role for sympathetic nerves to cutaneous vasodilatation during skin heating, growing evidence exists in support of this assertion (Houghton et al 2006;Hodges et al 2008Hodges et al , 2009bTew et al 2011b). In this context, we sought to examine whether sympathetic nerves were involved in the augmented cutaneous vasodilator response to noxious skin heating.…”
Section: Sympathetic Nervesmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from endothelial adaptations, changes in the sensitivity of vascular SMC to endothelial vasodilators or alterations in neural vascular control may play a role. By inducing local heating as a vasodilating stimulus, the study of Tew et al has shown that aerobic fitness affects the contribution of noradrenergic sympathetic fibers to the heating-induced LDF response (Tew et al, 2011). Indeed, it has been shown that endurance trained athletes have a diminished temperature threshold for active vasodilation i n s k i n c o m p a r e d t o m a t c h e d s e d e n t a r y controls (Fritzsche & Coyle, 2000).…”
Section: Exercise Augments the Endothelium Dependent Vasodilation In mentioning
confidence: 99%